Información Cartográfica del Departamento del Meta, Opción de Desarrollo Desde Aspecto Socioeconómicos Territoriales y Ambientales: Caso Municipio de Mesetas (2019)
It establishes the minors for the development of an agricultural software for the department of Meta that initiates a pilot phase in the municipality of Mesetas which has the potential to present territorial, economic, productive, sociocultural and environmental information that will be used by farmers, producers professors and government officials in order to make decisions adjusted to the realities in favor of sustainable and sustainable economic growth and development. To this end, a data collection was carried out using the participatory action methodology from each of the aforementioned variables that formed the basis for the construction of information stored in cartographic software, which was called the SISCARTAGRO agricultural cartographic system, constituting a reliable tool for innovative development, every time; presents territorial realities from a multidimensional approach. Definitely the agricultural cartographic system is presented as a determining factor in the development of production and territorial development in the department of Meta, since this territory has historically hosted a socio-economic vocation that must be strengthened with strategies designed from the realities of the Territories, not because of a whim of experts and / or any protagonist with good intentions, making ill-advised decisions, since they do not correspond to the territorial realities of the present populations.